Wnt signalling pathways in chronic lymphocytic leukaemia and B-cell lymphomas - Janovská, Pavlína; Bryja, Vítězslav (British journal of pharmacology, 2017)
UNLABELLED: In this review, we discuss the intricate roles of the Wnt signalling network in the development and progression of mature B-cell-derived haematological malignancies, with a focus on chronic lymphocytic leukaemia (CLL) and related B-cell lymphomas. We review the current literature and highlight the differences between the β-catenin-dependent and -independent branches of Wnt signalling. Special attention is paid to the role of the non-canonical Wnt/planar cell polarity (PCP) pathway, mediated by the Wnt-5-receptor tyrosine kinase-like orphan receptor (ROR1)-Dishevelled signalling axis in CLL. This is mainly because the Wnt/PCP co-receptor ROR1 was found to be overexpressed in CLL and the Wnt/PCP pathway contributes to numerous aspects of CLL pathogenesis. We also discuss the possibilities of therapeutically targeting the Wnt signalling pathways as an approach to disrupt the crucial interaction between malignant cells and their micro-environment. We also advocate the need for research in this direction for other lymphomas, namely, diffuse large B-cell lymphoma, Hodgkin lymphoma, mantle cell lymphoma, Burkitt lymphoma and follicular lymphoma where the Wnt signalling pathway probably plays a similar role. LINKED ARTICLES: This article is part of a themed section on WNT Signalling: Mechanisms and Therapeutic Opportunities. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v174.24/issuetoc.
Keywords: Lymphoma, B-Cell; Wnt Signaling Pathway; Animals; Leukemia, Lymphocytic, Chronic, B-Cell; lidé; zvířata; signální dráha Wnt; chronická lymfatická leukemie; B-buněčný lymfom; Humans